DAMPAK KEGIATAN REHABILITASI HUTAN DAN LAHAN TERHADAP KESEJAHTERAAN MASYAKARAT SEKITAR HUTAN DI KABUPATEN BENGKAYANG - B61112017, HEPPY YUBILANCE (Jurnal Ekonomi Daerah (JEDA), 2016)
This study aims to determine how the influence of forest and land rehabilitation activities (RHL) on the welfare of forest villagers in Bengkayang. The research method uses descriptive research with a case study in the district of Bengkayang, especially in districts that do RHL activities. The researchers intend to acquire in-depth description of the condition of the people who suffered damage to land. The impact of the policy does RHL and the factors that hinder the policy in question. The study used secondary data obtained from BPS Office Bengkayang and West Kalimantan. While the primary data by direct interviews with respondents. The results of the analysis of different test average can be concluded that the level of people's income, health and access to bank credit before and after the Forest and Land Rehabilitation activity significantly different significantly. After their activities in Bengkayang RHL income levels increased on average by Rp3.500.000 each month. If converted at a purchase price of rice per kg on average Rp. 9.500, - / kg, each respondent will receive 368 kg of rice, that income of the people in the region is above the income poor RHL (240 Kg).Â Keywords : Forest and Land Rehabilitation